Cytochrome P450 4B1 (CYP4B1) as a target in cancer treatment - Sharoen Lim, Yu Ming; M., Alshagga; C. E., Ong; J. Y., Chieng; Y., Pan (SAGE Publications, 2020)
Cytochrome P450 4B1 (CYP4B1) plays crucial roles in biotransforming of xenobiotics. Its predominant extrahepatic expression has been associated with certain tissue-specific toxicities. However, the expressions of CYP4B1 in various cancers and hence their potential roles in cancer development were inclusive. In this work, existing knowledge on expression and regulation of CYP4B1 gene and protein, catalysis of CYP4B1, association of CYP4B1 with cancers, contradicting findings about human CYP4B1 activities as well as the employing CYP4B1 in suicide gene approach for cancer treatment were reviewed. To date, it appears that there is a wide spectrum of tissue distribution of CYP4B1 with lungs as the predominant sites. Several nuclear receptors are possibly responsible for regulating its gene expression. The involvement of CYP4B1 in cancer was considered via activation of procarcinogens and neovascularization. However, human CYP4B1 was found to be inactive due to a substitution of proline with serine at position 427. Suicide gene approach combining reengineered CYP4B1 and prodrug 4-ipomeanol (4-IPO) has shown a promising potential for targeted cancer therapy. Further studies should focus on the verification of human CYP4B1 catalytic activities. More compounds with similar structure as 4-IPO should be tested to identify more alternative agents for the suicide gene approach in cancer treatment.